Mites (Acari: Mesostigmata, Sarcoptiformes and Trombidiformes) associated to soybean in Brazil, including new records from the cerrado areas - Rezende, Jose Marcos [UNESP] (2012)
In Brazil, soybean Glycine max (L.) Merril crops are subjected to incidence of several pests, which are mainly insect species. However, the occurrences of other pest species are growing. In this context, outbreaks of phytophagous mites are becoming more frequent. Nevertheless, records of mites in such crop are available only for Maranhao, Mato Grosso, Minas Gerais and Rio Grande do Sul states. Thus, this work gathers all information published about the diversity of mites found in soybean in Brazil, and also new records of mite species made on samplings taken from the central Cerrado area. In the whole, occurrence of 44 species of plant mites in soybean has been recorded in Brazil. Data from prior studies and the results of this work present the tetranychid Mononychellus planki (McGregor) as the mite species most frequently occurring in the Brazilian soybean crops. A large portion of Phytoseiidae species has occurred in crops from Rio Grande do Sul state. In addition, spontaneous soybean has hosted almost half of the phytoseiid species sampled in Cerrado region. High diversity of Tarsonemidae has been found in the cultivated soybean. More studies about soybean mites are needed to clarify the damage potential of phytophagous mites and the biological role of predatory mites in this crop.